Tanoker community as a counter culture movement to communicate traditional games in Ledokombo Jember Indonesia - Juariyah Juariyah; Putri Robiatul Adawiyah (Universitas Negeri Yogyakarta, 2022)
Tanoker is one of the traditional games in Indonesia which is one of the cultural heritages whose existence must be protected and preserved. The Tanoker community has begun to actively promote this traditional game to be introduced to the community. The purpose of this study is to examine the Tanoker community in their efforts to prevent the negative impact of online gaming culture through traditional games. This type of research using in this study is a qualitative approach with ethnographic methods was used in this study as well as by analyzing the text and interview results. The results showed that the Tanoker community played a role in communicating the traditional game of tanoker in the community as a counter culture movement to communicate traditional games in Ledokombo Jember. The Tanoker Ledokombo community is not anti-modern games, some of them who come with cell phones, there are only rules when activities are being carried out, their cell handphones cannot be used. This is where good values are internalized in children Tanoker aims to contribute solving problems, especially preparing children to live healthy, fostering a cooperative, discipline, and sportive sense, being smart and having prosperous lives.